Thiothrix and Sulfurovum genera dominate bacterial mats in Slovak cold sulfur springs - Lea Nosalova; Chahrazed Mekadim; Jakub Mrazek; Peter Pristas (Environmental Microbiome, 2023)
Abstract Microbiota of sulfur-rich environments has been extensively studied due to the biotechnological potential of sulfur bacteria, or as a model of ancient life. Cold terrestrial sulfur springs are less studied compared to sulfur-oxidizing microbiota of hydrothermal vents, volcanic environments, or soda lakes. Despite that, several studies suggested that sulfur springs harbor diverse microbial communities because of the unique geochemical conditions of upwelling waters. In this study, the microbiota of five terrestrial sulfur springs was examined using a 16 S rRNA gene sequencing. The clear dominance of the Proteobacteria and Campylobacterota phyla of cold sulfur springs microbiota was observed. Contrary to that, the microbiota of the hot sulfur spring was dominated by the Aquificota and Firmicutes phylum respectively. Sulfur-oxidizing genera constituted a dominant part of the microbial populations with the Thiothrix and Sulfurovum genera identified as the core microbiota of cold sulfur terrestrial springs in Slovakia. Additionally, the study emphasizes that sulfur springs in Slovakia support unique, poorly characterized bacterial communities of sulfur-oxidizing bacteria.